Comparison of Code-Pass-Skipping Strategies for Accelerating a JPEG 2000 Decoder - Bruns, Volker; Sparenberg, Heiko (Technische Universität Dortmund, 2013)
Code-Pass-Skipping allows a JPEG 2000 decoder to be accelerated by sacrificing the output precision. This paper presents an evaluation on how the speed gain can be maximized and the quality loss minimized. In particular, the scenario of rendering a 24-bit preview of a Digital Cinema Package (DCP) with the maximum permitted bitrate is examined. A comparison shows, that a new proposed strategy outperforms the reference implementation from Kakadu Software v6 by up to 1 dB. Furthermore, it is shown what speed gain can be achieved for a given acceptable quality loss.
Keywords: 620